ANALISIS PEMAHAMAN MAHASISWA PENDIDIKAN FISIKA UNIVERSITAS JEMBER MELALUI MULTIREPRESENTASI VERBAL DAN GRAFIK TENTANG MANFAAT DAN BAHAYA SINAR UV BAGI KESEHATAN - Elma Tri Istighfarini; Sudarti; Yushardi (LPPM Universitas Gunung Rinjani, 2021)
This study aims to analyze the understanding of Physics Education students at the University of Jember regarding the benefits and dangers of UV rays for health through multi-representation graphs and graphs. This study used a descriptive method with a quantitative approach through questionnaires to 50 students of Physics Education at the University of Jember, namely the 2nd semester students and 4th semester students.The data sources were obtained from a multiple choice questionnaire which included 10 verbal and graphic questions with 5 verbal questions and 5 questions. validated graph questions. The results of respondents' answers will be analyzed in describing the ability of Physics Education students at the University of Jember in understanding the benefits and dangers of UV rays for health through verbal and graphic multi-representation. Based on research that has shown that Physics Education students at the University of Jember better understand the material given or seen in questions with graphical representation results, it is seen from the average value of correct answers to verbal representation questions of 71.06% and the average correct answers for about graph representation of 39.76%. The percentage of 71.06% indicates that not all Physics Education students at the University of Jember understand the benefits and dangers of UV rays for health. This is because the sun in semester 2 students has not been given courses that discuss radiation and the small percentage of correct answers with graphical representations because the level of difficulty of the questions is higher related to questions of verbal representation. Keywords: UV radiation, Benefit of UV rays, Danger of UV Rays, Verbal Representation, Graphic Representation ABSTRAK Penelitian ini bertujuan untuk menganalisis pemahaman mahasiswa Pendidikan Fisika Universitas Jember mengenai manfaat dan bahaya sinar UV bagi kesehatan melalui multirepresentasi verbal dan grafik . Penelitian ini menggunakan metode deskriptif dengan pendekatan kuantitatif melalui kuisioner terhadap 50 mahasiswa Pendidikan Fisika Universitas Jember yaitu pada mahasiswa semester 2 dan mahasiswa semester 4. Sumber data diperoleh dari kuisioner berbentuk pilihan ganda yang meliputi soal verbal dan grafik sebanyak 10 soal dengan 5 soal verbal dan 5 soal grafik yang telah divalidasi. Hasil jawaban responden akan dianalisis dalam mendeskripsikan kemampuan mahasiswa Pendidikan Fisika Universitas Jember dalam memahami manfaat dan bahaya sinar UV bagi kesehatan melalui multirepresentasi verbal dan grafik. Berdasarkan hasil penelitian yang telah dilakukan menunjukkan bahwa mahasiswa Pendidikan Fisika Universitas Jember lebih memahami materi yang diberikan atau dilihat dalam bentuk soal dengan representasi verbal daripada representasi grafik yaitu dilihat dari nilai rata – rata jawaban benar soal representasi verbal sebesar 71,06% dan rata – rata jawaban benar untuk soal representasi grafik sebesar 39,76%. Prosentase sebesar 71,06 % menunjukkan bahwa tidak semua mahasiswa Pendidikan Fisika Universitas Jember memahami manfaat dan bahaya Sinar UV bagi kesehatan. Hal ini dikarenakan pada mahasiswa semester 2 belum diberikan mata kuliah yang membahas mengenai radiasi matahari dan kecilnya prosentasi jawaban benar dengan representasi grafik karena tingkat kesulitan soal lebih tinggi daripada soal dengan representasi verbal. Kata kunci: Radiasi UV; Manfaat Sinar UV; Bahasa Sibar UV; Bahasa sinar UV; Representasi Verbal; Representasi Grafik;